Improved monitoring of oriental fruit moth (Lepidoptera: Tortricidae) with terpinyl acetate plus acetic acid membrane lures. (2nd June 2018) - Mujica, Valentina; Preti, Michele; Basoalto, Esteban; Cichon, Liliana; Fuentes‐Contreras, Eduardo; Barros‐Parada, Wilson; Krawczyk, Greg; Nunes, Marcelo Z.; Walgenbach, Jim F.; Hansen, Randy; Knight, Alan L.
Abstract: Male and female moth catches of Grapholita molesta (Busck) in traps were evaluated in stone and pome fruit orchards untreated or treated with sex pheromones for mating disruption in Uruguay, Argentina, Chile, USA, and Italy from 2015 to 2017. Trials evaluated various blends loaded into either membrane cup lures or septa. Membrane lures were loaded with terpinyl acetate (TA), acetic acid (AA) and ( Z )‐3‐hexenyl acetate alone or in combinations. Two septa lures were loaded with either the three‐component sex pheromone blend for G. molesta alone or in combination with codlemone (2‐PH), the sex pheromone of Cydia pomonella (L). A third septum lure included the combination sex pheromone blend plus pear ester, ( E, Z )‐2, 4‐ethyl decadienoate (2‐PH/PE), and a fourth septum was loaded with only β‐ocimene. Results were consistent across geographical areas showing that the addition of β‐ocimene or ( Z )‐3‐hexenyl acetate did not increase moth catches. The addition of pear ester to the sex pheromone lure marginally increased moth catches. The use of TA and AA together significantly increased moth catches compared with the use of only one of the two components. Traps with the TA/AA lure outperformed the Ajar trap baited with a liquid TA plus sugar bait. The emission rate of AA was not a significant factor affecting the performance of the TA/AA lure. The addition of TA/AA significantly increased moth catches when combined with the 2‐PH lure. The TA/AA lure also allowed traps to catch both sexes. Catch of C. pomonella with the 2‐PH lure was comparable to the use of codlemone; however, moth catch was significantly reduced with the 2‐PH/PE lure. Optimization of these complex lures can likely further improve managers' ability to monitor G. molesta and help to develop multispecies tortricid lures for use in individual traps.